Development of energy-saving devices for a full slow-speed ship through improving propulsion performance - Jung-Hun Kim (International Journal of Naval Architecture and Ocean Engineering, 2015)
Energy-saving devices for 317 K VLCC have been developed from a propulsion standpoint. Two ESD candidates were designed via computational tools. The first device WAFon composes of flow-control fins adapted for the ship wake to reduce the loss of rotational energy. The other is WAFon-D, which is a WAFon with a duct to obtain additional thrust and to distribute the inflow velocity on the propeller plane uniform. After selecting the candidates from the computed results, the speed performances were validated with model-tests. The hydrodynamic characteristics of the ESDs may be found in improved hull and propulsive efficiencies through increased wake fraction.